ChemInform Abstract: Synthesis of Quinazolines and Dihydroquinazolines: o‐Iodoxybenzoic Acid Mediated Tandem Reaction of o‐Aminobenzylamine with Aldehydes. Issue 38 (September 2016) - Hati, Santanu; Sen, Subhabrata
Abstract: By simply altering the amount of the IBX reagent, either quinazolines or 3, 4‐dihydroquinazolines are accessible in good to high yields.